Heterogeneous photocatalysis at liquid–solid interfaces. Oxidative dehydrogenation of propan-2-ol as a method of assessing photocatalytic activity? - Bickley, Roger I. (Journal of photochemistry and photobiology. A, Chemistry., 2010)
Heterogeneous photocatalysis has developed significantly since its discovery about 100 years ago. Using the number of published papers as an index, the subject progressed slowly in the first 50 years, since which it has become much more prolific. Accompanying the increase in publications has been increases in the number of research centres undertaking studies in this area with diversities of reactions studied, light sources used, photocatalytic materials prepared, and experimental conditions adopted. The quantification of kinetic data, in the form of reaction rate constants and quantum efficiencies, has been inevitably subject to variability as a consequence. In an attempt to overcome these limitations, it was suggested by Bickley (1980), and reiterated by Teichner (1985) that a standard calibration reaction should be used to reduce the variability. Criteria for a standard reaction should be an intrinsic chemical simplicity, product analysis by a widely available method, and the use of a commonly available photocatalytic material. Progress has been made towards achieving these objectives, with the oxidative dehydrogenation of propan-2-ol to propan-2-one at powdered titanium dioxide surfaces being one method currently considered suitable for this purpose. The attractiveness of this reaction is that propan-2-one can be quantified below micro-molar concentrations by gas–liquid chromatography, a widely available technique. Furthermore the kinetic behaviour of this photocatalytic reaction is strictly pseudo-zero-order for a diverse range of titanium dioxide preparations. The objective of this article is to describe the main features of a carefully controlled investigation of this reaction and, as a result, other features are revealed that suggest the conditions under which it is used for the purposes of calibration should be carefully defined.